Integrative brain structural and molecular analyses of interaction between tobacco use disorder and overweight among male adults. Issue 2 (5th November 2022) - Zhang, Mengzhe; Gao, Xinyu; Yang, Zhengui; Niu, Xiaoyu; Wang, Weijian; Han, Shaoqiang; Wei, Yarui; Cheng, Jingliang; Zhang, Yong
Abstract: Tobacco smoking and overweight lead to adverse health effects, which remain an important public health problem worldwide. Researches indicate overlapping pathophysiology may contribute to tobacco use disorder (TUD) and overweight, but the neurobiological interaction mechanism between the two factors is still unclear. This study used a mixed sample design, including the following four groups: (i) overweight long‐term smokers ( n = 24, age = 31.80 ± 5.70, cigarettes/day = 20.50 ± 7.89); (ii) normal weight smokers ( n = 28, age = 31.29 ± 5.56, cigarettes/day = 16.11 ± 8.35); (iii) overweight nonsmokers ( n = 19, age = 33.05 ± 5.60), and (iv) normal weight nonsmokers ( n = 28, age = 31.68 ± 6.57), a total of 99 male subjects. All subjects underwent T1‐weighted high‐resolution MRI. We used voxel‐based morphometry to compare gray matter volume (GMV) among the four groups. Then, JuSpace toolbox was used for cross‐modal correlations of MRI‐based modalities with nuclear imaging derived estimates, to examine specific neurotransmitter system changes underlying the two factors. Our results illustrate a significant antagonistic interaction between TUD and weight status in left dorsolateral prefrontal cortex (DLPFC), and a quadratic effect of BMI on DLPFC GMV. For main effect of TUD, long‐term smokers were associated with greater GMV in bilateral OFC compared with nonsmokers irrespective of weight status, and such alteration is negatively associated with pack‐year and FTND scores. Furthermore, we also found GMV changes related to TUD and overweight are associated with μ‐opioid receptor system and TUD‐related GMV alterations are associated with noradrenaline transporter maps. This study sheds light on novel multimodal neuromechanistic about the relationship between TUD and overweight, which possibly provides hints into future treatment for the special population of comorbid TUD and overweight. Abstract : This study illustrates a significant antagonistic interaction between tobacco use disorder (TUD) and weight status in left dorsolateral prefrontal cortex (DLPFC), and a quadratic effect of body mass index on DLPFC gray matter volume. These results possibly provide hints into future treatment for the special population of comorbid TUD and overweight.